2020
DOI: 10.1002/adma.201904320
|View full text |Cite
|
Sign up to set email alerts
|

Sodium/Potassium‐Ion Batteries: Boosting the Rate Capability and Cycle Life by Combining Morphology, Defect and Structure Engineering

Abstract: Carbon‐based materials have been considered as the most promising anode materials for both sodium‐ion batteries (SIBs) and potassium‐ion batteries (PIBs), owing to their good chemical stability, high electrical conductivity, and environmental benignity. However, due to the large sizes of sodium and potassium ions, it is a great challenge to realize a carbon anode with high reversible capacity, long cycle life, and high rate capability. Herein, by rational design, N‐doped 3D mesoporous carbon nanosheets (N‐CNS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
254
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 370 publications
(263 citation statements)
references
References 87 publications
(137 reference statements)
8
254
1
Order By: Relevance
“…This can be understood as the broadening of interlayer after potassium insertion at a low current density. [36] Furthermore, the pyrrolic and pyridinic N-induced defects are active sites for adsorbing potassium ions. With the adsorption of potassium ions at the active sites, the defects decrease, leading to the decrease of I D /I G value.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be understood as the broadening of interlayer after potassium insertion at a low current density. [36] Furthermore, the pyrrolic and pyridinic N-induced defects are active sites for adsorbing potassium ions. With the adsorption of potassium ions at the active sites, the defects decrease, leading to the decrease of I D /I G value.…”
Section: Resultsmentioning
confidence: 99%
“…[26][27][28][29][30][31][32][33][34] As demonstrated by calculation and experimental study, the pyrrolic N and pyridinic N were suggested to be effective in enhancing the reversible capacity of the electrode. [18,[35][36][37][38] However, developing N-doped carbon materials with high concentration of easily accessible active N species (pyrrolic and pyridinic N) for enhanced PIBs performance still remains challenging.…”
Section: Introductionmentioning
confidence: 99%
“…As is shown, the spectrum of N 1s is deconvoluted into three peaks at ≈400.1 eV (N-5, Pyrrolic-N), ≈398.3 eV (N-6, Pyrindinic-6), and ≈401.5 eV (N-Q, Graphitic-N), respectively. [51][52][53] In S 2p spectrum, three deconvoluted peaks located at 161.5, 163.1, and 164.5 eV, corresponding to S 2p 3/2 , S 2p 1/2 , and C-S bonds, respectively. [54,55] This is positive because strong coupling effect will occur at the heterointerface due to the heteroatoms doping induced electron cloud bias, thereby effectively accelerating the electron transport and offering more active sites for Na + /K + storage.…”
Section: Morphology and Structure Characterizationmentioning
confidence: 99%
“…are consisted of a semicircle at the high-to medium-frequency region and an inclined straight line at the low-frequency region. According to previous literature, the semicircle belongs to the resistance of SEI film (R SEI ) and the charge-transfer resistance (R ct ), [43,44,45] and the straight line can be assigned to the lithium ion diffusion in electrodes, known as the Warburg impedance (Z w ). [46,47,48] As shown in Figure 6a, in comparison to Si@C anodes, the Si@CÀ Co 9 S 8 /C anodes show the relative lower R ct , suggesting high electrical conductivity of the Si@CÀ Co 9 S 8 /C anodes.…”
Section: Lithium Storage Performance Characterizationmentioning
confidence: 99%